Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination - Yasunaga, Tomohide; Nakatani, Yukinobu; Chérot, Frédéric (Zootaxa, 2017)
Species of the Old World mirine plant bug genus Eurystylus Stål (the Head Bugs) in Japan and Taiwan are reviewed. Four species are currently recognized. Two new species are diagnosed and described: E. ryukyus n. sp. (from SW Japan and Taiwan) and E. jingfui n. sp. (Taiwan). Two known species, E. coelestialium (Kirkaldy) and E. sauteri Poppius, are diagnosed; new distributional records are added for the latter. Two keys are provided to aid the identifications of (1) Eurystylus and four related genera and (2) the species of Eurystylus known from Japan and Taiwan. The phylogenetic relationships of Eurystylus with the assumed related genera are discussed. Eurystylomorpha Poppius is synonymized with Eurystylopsis Poppius, and a new combination, Eurystylopsis crassicornis (Poppius), is accordingly proposed.